Differences in Work Plans of Graduating Family Medicine Residents - Allingham, J.D. (1985)
Much subjective evidence has compared productivity of male and female physicians. Given that enrollment of female students is now much higher, manpower planners have to look carefully at the implications, ensuring that they have accurate information. This study surveyed 1984 graduates of one Ontario and four western residency training programs in family practice. Although many men had no fulltime plans and intended to take at least three months off, women were more likely not to have any work plans, to be intending to practice in an urban area, and to be intending to limit their practices (e.g. no obstetrics, no emergency room, no surgical assisting). While traditional role conflicts may account for these differences, there may also be different confidence levels by sex for certain aspects of family medicine.